Respuesta :

3x^2 + 8x - 2 = 2x^2 - 4x - 32
You are going to want to move all the numbers to one side and set it equal to 0. Combine any similar terms. (Ex: 2x^3 and 6x^3, they are similar so you can add them together.)
x^2 + 12x + 30 = 0
Then you are going to use the quadratic formula to solve. a=1 b=12 c=30
x = -b +- √b^2 - 4ac / 2a
x = -(12) +- √(12)^2 - 4(1)(30) / 2(1)
x = -12 +- √24 / 2
Then simplify!
x = -6 + √6 and x = -6 - √6

Hope that I was able to help and that you understand everything. If you have any questions, feel free to ask! Good luck! :)
ACCESS MORE